(untitled) (FULafia Journal of Science and Technology, 2020)
This study assessed the efficacy and safety of albendazole (ALB) amongst soil-transmitted helminth (STH) infected school aged children (SAC) cross-section ally in Odeda Local Government Area (LGA), Ogun State, Nigeria. Consented 485 pupils between the ages of 5 – 16 years were examined for STH infections using the Kato-katz technique at baseline. All consented SAC were treated to a single dose (400mg) of ALB. Closeended questionnaires on safety of ALB administered to SAC, 24 hours after ingestion. Stool samples were collected at 3-weeks post treatment to re-examine for Egg Reduction Rate (ERR) and Cure Rate (CR). The results were analyzed using SPSS version 20 with Chi-square set at p = 0.05 to compare relationship between demography factors and prevalence. Of the 485 pupils, an overall prevalence of 138(28.5%) were found to be infected with various species of STH infections.